The conceptual design of a stream island index for physical habitat complexity assessment in stream restoration projects - Tallar, Robby Yussac (Frontiers in Built Environment, 2023)
Most literature on geomorphology, hydraulics, or stream ecology contained either no mention or a brief description of stream islands, the process, the development, or the ecological advantages provided. Due to a lack of information, research, and related data, there were no stream island indexes available to indicate the stream island status. Motivated by this fact, the objective of this study is to develop a conceptual design for a Stream Island Index (SII) as a template for physical habitat complexity assessment in stream restoration projects. Specific purposes included: 1) to examine stream island conceptual models; 2) to develop obvious and comprehensive explanations for stream island development by considering attributes from the geomorphic, hydraulic, and ecological perspectives. This study used the AHP method for screening and selecting attributes, transforming and developing sub-indices, assigning weights, and formulating an index. The conclusion is an SII that combines the measures of selected physical habitat quality indicators to produce a single dimensionless number, and a novel approach to communicate information on stream island quality status to the public and related policymakers. It seems essential that a serious attempt be developed to design a system that can identify the overall stream island condition. Once a generalized stream island system is set up as a controlling framework, supplementary indexes for specific purposes and locations can be added. Therefore, the SII is a promising new tool for stream restoration practitioners, and it has the potential to make a significant contribution to improving the success of stream restoration projects.